1986
DOI: 10.1203/00006450-198602000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Arginine Vasopressin: Pattern of Excretion in the Neonatal Period

Abstract: ABSTRACT. The pattern of arginine vasopressin (AVP) secretion in the immediate neonatal period is unclear. Plasma concentrations of AVP are reflected by its urinary excretion, thus providing a noninvasive method for studying the pattern of AVP release in the neonate. In these studies, we determined the pattern of urinary AVP excretion (pU/ mg creatinine) during the first 2-4 days after birth in 78 neonates, 53 of whom had various prenatal and/or neonatal complications. In well term ( n = 12) and preterm (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…Our findings are confirmed by one other study [17], This group, however, used the AVP radioimmunoassay which we devel oped and so further studies with different radioimmunoassay systems should be per formed. In general it can be said that se verely ill newborns with RDS have a great risk of overhydration because of nonosmotic release of AVP.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings are confirmed by one other study [17], This group, however, used the AVP radioimmunoassay which we devel oped and so further studies with different radioimmunoassay systems should be per formed. In general it can be said that se verely ill newborns with RDS have a great risk of overhydration because of nonosmotic release of AVP.…”
Section: Discussionsupporting
confidence: 80%
“…Many data have been collected in the last few years to gain a better under standing of the pathophysiology of water me tabolism [8,17]. Renal function, changes in body composition and hormonal influences have been studied to define the term ade quate in regard to fluid management in pre term infants.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal stress as indicated by meconiumpresent in the amniotic fluid is associated with elevated cord AVP levels [10], but the effect of birth on asphyxia in elevating AVP levels [11] only lasts for the first 2 days [12]. The type of delivery also influences AVP levels [13], vaginal delivery versus caesarean section being associated with higher levels [14].…”
Section: Discussionmentioning
confidence: 99%
“…In one series [17], comparison of results from three groups of preterm infants demonstrated that those with RDS were unable to excrete the administered fluid, gained weight and developed hyponatraemia. In animal models positive pressure ventilation is also a stimulus for AVP release [18], but the effect of ventilation on AVP levels in the human is debated [3,11,[19][20][21]. In one study [3] continuous sequential urinary arginine vasopressin measurement in 14 preterm ventilated infants demonstrated that AVP levels increased during deterioration of the respiratory illness, mask ventilation and the development of bilateral pneumothoraces or severe intraventricular haemorrhage [3].…”
Section: Discussionmentioning
confidence: 99%
“…A VP Release Recent studies on the pattern of AVP secretion in the immediate neonatal period have shown higher cord plasma AVP con centrations in newborn infants born vaginally than in those delivered by cesarean sec tion [9] and perinatal complication such as asphyxia [27], hypoxic-ischemic encephalop athy [12], intracranial hemorrhage [1], se vere respiratory distress [38], pneumotho rax, pneumonia, atelectasis [20,30], and meningitis [19] have been reported to be associated with elevated plasma and urinary AVP concentrations. The inappropriate se cretion of AVP related to perinatal pathol ogy is thought to be an important cause of the early type of hyponatremia which fre quently occurs in the first week of life [18].…”
Section: Observations In Human Neonatesmentioning
confidence: 99%